2011
DOI: 10.1016/j.hydromet.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of dissolution of synthetic covellite, chalcocite and digenite in dilute chloride solutions at ambient temperatures

Abstract: . (2011) The kinetics of dissolution of synthetic covellite, chalcocite and digenite in dilute chloride solutions at ambient temperatures. Hydrometallurgy, This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 20 publications
8
43
0
Order By: Relevance
“…The range of Eh was chosen based on heap bioleaching practices (Ruan et al, 2013), and the values set were greater than the rest potential of chalcocite reported at approximately 600 mV (Miki et al, 2011;Petersen and Dixon, 2003).…”
Section: Effect Of Ehmentioning
confidence: 99%
See 3 more Smart Citations
“…The range of Eh was chosen based on heap bioleaching practices (Ruan et al, 2013), and the values set were greater than the rest potential of chalcocite reported at approximately 600 mV (Miki et al, 2011;Petersen and Dixon, 2003).…”
Section: Effect Of Ehmentioning
confidence: 99%
“…Oxidative dissolution of chalcocite by Fe 3+ , O 2 or Cu 2+ , either in a sulfate or chloride system, occurs in two distinct stages with the production of secondary covellite (Cu 1.0-1.2 S) as an intermediate (Bolorunduro, 1999;Cheng and Lawson, 1991a;Dutrizac and MacDonald, 1974;Mao and Peters, 1983;Mcdonald and Langer, 1983;Miki et al, 2011;Mulak and Niemiec, 1969;Petersen and Dixon, 2003;Ruan et al, 2013;Ruiz et al, 1998Ruiz et al, , 2007Senanayake, 2007Senanayake, , 2009Sullivan, 1930;Thomas et al, 1967):…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the second peak at 0.529 V is lower than that of the covellite or chalcocite oxidation peaks. Miki et al [10] indicated that covellite, which is produced from chalcocite oxidation, is more easily oxidized than crystalline covellite. The second peak may be a covellite oxidation peak that is produced from chalcocite oxidation.…”
Section: Evaluation Of the New Electrode Systemmentioning
confidence: 99%